Pharmacokinetic interactions between glimepiride and rosuvastatin in healthy Korean subjects: does the SLCO1B1 or CYP2C9 genetic polymorphism affect these drug interactions? - Kim, Choon Ok (Drug Des Devel Ther, 2017)
To improve cardiovascular outcomes, dyslipidemia in patients with diabetes needs to be treated. Thus, these patients are likely to take glimepiride and rosuvastatin concomitantly. Therefore, this study aimed to evaluate the pharmacokinetic (PK) interactions between these two drugs in healthy males and to explore the effect of SLCO1B1 and CYP2C9 polymorphisms on their interactions in two randomized, open-label crossover studies. Glimepiride was studied in part 1 and rosuvastatin in part 2. Twenty-four participants were randomly assigned to each part. All subjects (n=24) completed part 1, and 22 subjects completed part 2. A total of 38 subjects among the participants of the PK interaction studies were enrolled in the genotype study to analyze their SLCO1B1 and CYP2C9 polymorphisms retrospectively (n=22 in part 1, n=16 in part 2). Comparison of the PK and safety of each drug alone with those of the drugs in combination showed that both glimepiride and rosuvastatin did not interact with each other and had tolerable safety profiles in all subjects. However, with regard to glimepiride PK, the SLCO1B1 521TC group had a significantly higher maximum plasma concentration (C(max,ss)) and area under the plasma concentration–time curve during the dose interval at steady state (AUC(τ,ss)) for glimepiride in combination with rosuvastatin than those for glimepiride alone. However, other significant effects of the SLCO1B1 or CYP2C9 polymorphism on the interaction between the two drugs were not observed. In conclusion, there were no significant PK interactions between the two drugs; however, the exposure to glimepiride could be affected by rosuvastatin in the presence of the SLCO1B1 polymorphism.